INTEGRASI TEKNOLOGI MELALUI MEDIA VIDEO ANIMASI INTERAKTIF DAN PENGARUHNYA TERHADAP HASIL BELAJAR SISWA DALAM PELAJARAN SOSIOLOGI FASE E DI SMA N 5 TEBO - Lestari, Melita Eka; Hefni; Wahyuni, Yanti Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of students in Sociology. This study aims to determine the influence of Technology Integration Through Interactive Animated Video Media on Student Learning Outcomes in Sociology Subject Phase E at SMA N 5 Tebo. The theory used in this research is cognitive theory, which is a learning theory that understands how individuals acquire, store, and use knowledge. The research method used in this study is quantitative with a Quasi-Experimental Design. Data collection techniques used were questionnaires, multiple-choice tests, and observations. The research findings were processed using a t-test. Hypothesis: The research findings show that: Based on the study conducted, it was found that there is an influence of Technology Integration Through Interactive Animated Video Media on Student Learning Outcomes in Sociology Subject Phase E at SMA N 5 Tebo. This can be seen from the average pretest score of the control group = 60.7 and the average posttest score of the control group = 71.4, and from the average pretest score of the experimental group = 67.6 and the average posttest score of the experimental group = 85. The t-calculated value for the interactive animated video media variable (X) is 2.045 and the t-table value is 25.165, thus yielding the result that 2.045 > 25.165. The significance value of the learning outcomes variable (Y) is less than 0.05, which is 0.000. The t-value and significance indicate that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant influence between the interactive animated video learning media variable (X) and learning outcomes (Y).